Beta3Gn-T7 Is a Keratan Sulfate β1,3 N-Acetylglucosaminyltransferase in the Adult Brain - Yoshiko Takeda-Uchimura; Kazuchika Nishitsuji; Midori Ikezaki; Tomoya O. Akama; Yoshito Ihara; Fabrice Allain; Kenji Uchimura (Frontiers Media S.A., 2022)
Keratan sulfate (KS) glycan is covalently attached to a core protein of proteoglycans. KS is abundant in neuropils and presents densely in close proximity to the perineuronal region of the perineuronal net-positive neurons in the adult brain under physiological conditions. We previously showed that the synthesis of KS positive for the R-10G antibody in the adult brain is mediated by GlcNAc-6-sulfotransferase 3 (GlcNAc6ST3; encoded by Chst5). Deficiency in both GlcNAc6ST3 and GlcNAc6ST1, encoded by Chst2, completely abolished KS. Protein-tyrosine phosphatase receptor type z1 (Ptprz1)/phosphacan was identified as a KS scaffold. KS requires the extension of GlcNAc by β1,3 N-acetylglucosaminyltransferase (Beta3Gn-T). Members of the Beta3Gn-T family involved in the synthesis of adult brain KS have not been identified. In this study, we show by a method of gene targeting that Beta3Gn-T7, encoded by B3gnt7, is a major Beta3Gn-T for the synthesis of KS in neuropils and the perineuronal region in the adult brain. Intriguingly, the B3gnt7 gene is selectively expressed in oligodendrocyte precursor cells (OPCs) and oligodendrocytes similar to that of GlcNAc6ST3. These results indicate that Beta3Gn-T7 in oligodendrocyte lineage cells may play a role in the formation of neuropils and perineuronal nets in the adult brain through the synthesis of R-10G-positive KS-modified proteoglycan.